Integrating knowledge management and organizational spirituality in enhancing organizational practical wisdom - Rocha, Raysa Geaquinto (2022)
We need to reconcile business and society (Nonaka & Takeuchi, 2021; Porter & Kramer, 2011). This bridge must come from organizations that create shared value (Porter & Kramer, 2011). This need for change in the capitalist model and consequent organizational strategies is not new (Porter & Kramer, 2011; Schumacher, 1973). In recent decades, academics and practitioners have sought solutions with sustainability, innovation, and transcendence (Martin, 2015; Mckenna & Biloslavo, 2011; Varadarajan, 2017). The presence of practical wisdom (phronesis) in management research is increasing as construct nurturing experiences and behavior patterns that drive organizational change (Bierly et al., 2000; Mckenna & Biloslavo, 2011; McKenna & Rooney, 2019; Nonaka & Takeuchi, 2011, 2019, 2021; Rowley, 2006b). Aristotle (David Ross translation, ca. 350 B.C.E./2009, p. 106; 108) states that phronesis is “a reasoned and true state of capacity to act with regard to human goods”; and it is “concerned with things human and things about with it is possible to deliberate”. Regardless of its increasing appearance in the management literature, there is still a long way to understanding organizational practical wisdom. To successfully implement the transformations needed for companies to reconnect with society requires an understanding of how practical wisdom develops in organizations and how it interacts with other constructs (Akgün et al., 2019; Bierly et al., 2000; Rowley & Gibbs, 2008). Bierly et al. (2000) describe three pathways for building phronesis (i.e., personal experiences with the environment; spirituality that impacts faith, courage, and hope; the passion that provides self-efficacy). From the organizational perspective, "a practically wise organization is both a virtuous and a learning organization" (Rowley & Gibbs, 2008, p. 367). Spirituality is a dimension of human experience; it is a human phenomenon existing, at least potentially, in all individuals (Elkins et al., 1988, p. 8). Individual spirituality is the values, state of mind, way of being, and experiencing an awareness of a transcendent dimension (Elkins et al., 1988, p. 8). Bratianu (2015b) proposes that spiritual knowledge, a person's values, and future vision complement rational and emotional knowledge. Spiritual development brings meaning and purpose to organizational behavior and experiences (Benefiel, 2003; Bierly et al., 2000; Bratianu, 2015b; Kolodinsky et al., 2008). "Since meaning is essential to knowledge, purpose and values are central to knowledge creation and knowledge practice. Whether you are aware or not, you always create and practice knowledge for a certain end and based on certain values" (Nonaka & Takeuchi, 2019, p. 154). Therefore, organizational spirituality determines the identity of an organization (Rocha & Pinheiro, 2021a). In the knowledge society where an organization's most valuable resource is knowledge, it is necessary to understand knowledge dynamics, which are essential for organizations to incorporate desired changes successfully (Bolisani & Bratianu, 2018; Bratianu, 2015a; Nonaka & Takeuchi, 1995, 2019). It is crucial in spreading and fostering value alignment at the organizational level (Bolisani & Bratianu, 2018; Bratianu, 2015b). Knowledge management and organizational learning are fundamental to organizational practical wisdom (Bierly et al., 2000; Nonaka & Takeuchi, 2019; Rowley & Gibbs, 2008). Putting knowledge into action leads to understanding and experience, which is essential for developing practical wisdom (Aristotle, ca. 350 B.C.E./2009, trans David Ross). The main objective of this thesis is to answer the research question – How knowledge management and organizational spirituality support organizational practical wisdom? To answer the question, we have divided the research into three sections, i) theoretical, ii) mixed method, iii) quantitative. The first section presents the theoretical articles that aimed to establish the state of the art of research on the constructs (Chapter 2 and 3), propose the theoretical model to be studied (Chapter 2), establish the concept of organizational spirituality (Chapter 4), and suggest an approach to phronesis in the workplace integrated with workplace spirituality (Chapter 5). In Chapters 3 and 4, we used VOSviewer software version 1.6.16 for building, displaying, and exploring a bibliometric map supported by network data. In the empirical studies, we address specific gaps in leaders' awareness of the constructs (second section) and employees' perception of their relationships (third section). In the second section, we handled a mixed method research with 23 semi-structured interviews with organizations' leaders in 14 countries, using a thematic analysis and content analysis with software NVivo 12 assistances in the quantitative data analysis. It consists of two studies focusing on leaders' perceptions of organizational spirituality (Chapter 6) and organizational phronesis (Chapter 7). This section also offers contributions to business education (Chapter 7) as it is the best way to bring phronesis to organizations. Our main results show that leaders do not fully understand the constructs, making it challenging to develop them. Companies still need much advancement before they can incorporate practical wisdom. Addressing an academic and professional demand, we present the third section, in which we develop, validate (Chapter 8), and test (Chapter 9) the organizational practical wisdom scale. We adopted a mixed-method approach in Chapter 8, performing two studies with two samples, 199 answers from Portuguese speakers and 161 answers from English speakers. First, we conducted an Exploratory Factorial Analysis using IBM SPSS Statistics 27 software to instrument purification. Afterward, we performed a Confirmatory Factorial Analysis, using the SmartPLS 3.3.3 software to examine the scale validity, reliability, and latent structure. We procced the theoretical framework test in Chapter 9, examining the nomological validation of the organizational practical wisdom scale. This chapter investigates organizational spirituality as a mediator and moderator factor in the relationship between knowledge management and organizational phronesis. We especially targeted the potential that knowledge management and organizational spirituality hold in supporting the development of organizational practical wisdom. We collected data from 365 employees by online survey. We used the Smart PLS version 3.3.3 to conduct a partial least square structural equation modeling for testing our hypotheses and the IBM Statistics SPSS version 27 software to run the descriptive analysis. The scale is succinct with a more practical approach to the construct and can be used in organizations. Thus, academics and practitioners can continue learning and implementing practical organizational wisdom because it ought to be measurable. This thesis is pioneering in integrating knowledge management and organizational spirituality by empirically testing organizational phronesis. This process allowed us to link the constructs, understand how leaders and employees perceive them, and behave in organizations. The results support the direct effects of knowledge management and organizational spirituality on organizational phronesis and the indirect effect of knowledge management on organizational phronesis through the mediating and moderating effect of organizational spirituality. This thesis contributes to integrating knowledge management, organizational spirituality, and organizational practical wisdom theories and practices. Our outcomes contribute to identifying spirituality as a supplier of a comprehensive and integrative look beyond the constructs yet used in management. We note that this construct is increasingly present in organizations. Regarding knowledge management, the results identify a paradigm shift; the field moves from an initial phase focused on simply managing knowledge to integrated knowledge management focused on the values and principles that permeate knowledge and knowing a more holistic view of the company members and society. It indicates spirituality's role in this change, aligned with the emerging theory that includes a vision directed towards the future and society through a social strategy and efficiency in creating and sharing knowledge. Academics and practitioners ought to be aware of spirituality in business. Therefore, academics acknowledge the necessity to see the members as complete, spiritual beings, more than just resources for the company. Consequently, this thesis also contributes to illustrating the acknowledgment of the demand for a balance between the growth of tangible and intangible results in organizations. Hopefully, this subject continues in future research to disrupt the wild capitalistic paradigm in management, allowing us to be proud of the society we are building and handing over to the next generations. Forthcoming studies should focus on analyzing organizational practice rather than on the analysis of perceptions or discourse. Considering that all three constructs are action-oriented, it is necessary to analyze the actions of organizations and their members to capture the essence of spirituality and practical wisdom within organizations and the role played by knowledge management. Thus, case studies of both successes and failures need to be developed in diverse industries and cultures. To gain a deep understanding of how these constructs function in companies, academics and practitioners should cooperate to create strategies and means to integrate members with high-level values and prudent habits in the pursuit of a phronetic company. The future of research on phronesis in management lies in creating and improving strategies to consolidate organizational phronesis in everyday life. Only through the analysis of actions and their fruits will we understand how these constructs create shared value with society, enhancing innovation and sustainability. Thus, in further investigations into organizational wisdom practice and organizational spirituality, integration with these constructs and others, such as entrepreneurship, is necessary.